Participatory Leadership Styles Toward Employee Smoking Behavior In The Implementation Of Cigarette Areas In Inpositives Central Health Center In Tangerang City - Ani Fadmawaty; Viyan Septiana Ahmad (POLTEKKES KEMENKES PONTIANAK, 2020)
. Implementing the No Smoking Area policy, especially in health facilities, is still not optimal to reduce the smoking behavior of employees. Currently, there are still health workers or employees who still smoke. The head of the public-health center has an important role in implementing the no-smoking area policy, so an appropriate leadership style is needed aim, to get an overview of the relationship between the participatory leadership style of the head of the Puskesmas inpatient care because of implementing Non-Smoking Areas to the smoking behavior of its employees in Tangerang. The design of this study was a cross-sectional approach, by looking at the relationship between employee perceptions of the role of public-health center inpatient care leaders in implementing No Smoking Area policy and smoking behavior of inpatient public health centers in Tangerang City. As a result, most of the heads of the public-health center have non a participatory leadership style in implementing the No Smoking Area policy (61.3%) most of the public-health center staff had no smoking behavior (76.3%) and there was no relationship between the participatory leadership style of the head of the public-health center in implementing No Smoking Area policy the smoking behavior of public-health center employees at p = 0.123. In conclusion, there is no relationship between the participatory leadership style of the head of the health center in implementing the No Smoking Area policy and the smoking behavior of the health center employees..